Sustaining ecosystem services: Overcoming the dilemma posed by local actions and planetary boundaries - Jonas, Matthias; Ometto, Jean Pierre; Batistella, Mateus; Franklin, Oskar; Hall, Marianne; Lapola, David M. [UNESP]; Moran, Emilio F.; Tramberend, Sylvia; Queiroz, Bernardo Lanza; Schaffartzik, Anke; Shvidenko, Anatoly; Nilsson, Sten B.; et al. (Amer Geophysical Union, 2014)
Resolving challenges related to the sustainability of natural capital and ecosystem services is an urgent issue. No roadmap on reaching sustainability exists; and the kind of sustainable land use required in a world that acknowledges both multiple environmental boundaries and local human well-being presents a quandary. In this commentary, we argue that a new globally consistent and expandable systems-analytical framework is needed to guide and facilitate decision making on sustainability from the planetary to the local level, and vice versa. This framework would strive to link a multitude of Earth system processes and targets; it would give preference to systemic insight over data complexity through being highly explicit in spatiotemporal terms. Its strength would lie in its ability to help scientists uncover and explore potential, and even unexpected, interactions between Earth's subsystems with planetary environmental boundaries and socioeconomic constraints coming into play. Equally importantly, such a framework would allow countries such as Brazil, a case study in this commentary, to understand domestic or even local sustainability measures within a global perspective and to optimize them accordingly.
Keywords: Planetary Boundaries; Sustainability; Natural Capital; Ecosystem Functioning; Human Wellbeing; Environmental Perturbations